If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 100 = 5x + 75 Reorder the terms: 100 + 4x = 5x + 75 Reorder the terms: 100 + 4x = 75 + 5x Solving 100 + 4x = 75 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 100 + 4x + -5x = 75 + 5x + -5x Combine like terms: 4x + -5x = -1x 100 + -1x = 75 + 5x + -5x Combine like terms: 5x + -5x = 0 100 + -1x = 75 + 0 100 + -1x = 75 Add '-100' to each side of the equation. 100 + -100 + -1x = 75 + -100 Combine like terms: 100 + -100 = 0 0 + -1x = 75 + -100 -1x = 75 + -100 Combine like terms: 75 + -100 = -25 -1x = -25 Divide each side by '-1'. x = 25 Simplifying x = 25
| 15n^2-23n+6=0 | | x-15=4x+12 | | 6a-2a+10=2a+40 | | 6(2n+7)= | | -22(x-2)+44x=22(x+4)-44 | | 1306.6667=1/3*400*h | | 13w+39w^2=0 | | -3r^2+7f+6=0 | | 7x=200-3x | | -4(x+1)=7x-6+2(2x+7) | | 1n+7=n+7 | | 578756347856478678962676782652465246753-655742622575425476726537653765373567=k | | 9y+18=6x-3y | | 567542=8582j | | 9(7x-2)=-3x+2 | | -22(x-2)+44x=22(x+4)-4 | | 3(x-2)+1=-26 | | x=3g-fg | | 5h^2-9=0 | | 9(8x+11)=125 | | 40+12+0.25x=45+0.35x | | x/4-2=0 | | 9f^2-27f=0 | | -8u^2+3u+6=0 | | 3n-4n=-7 | | 3x-15=2y | | 2(3x-1)/5=5x-7/3 | | 4(1/5)=3p | | -5p+4=-2-8p-9p | | 4-2(x+5)=8x-2+4x | | x+3.9=1.8 | | x+3.9= |